Penerapan Teknik Relaksasi Benson Pada Asuhan Keperawatan Postpartum Sectio Caesarea Atas Indikasi Diabetes Melitus - Anisah Intan Safitri; Merida D Simanjuntak (AKPER Pasar Rebo, 2024)
Delivery by caesarean section can cause post-partum pain and discomfort. One of the actions taken to reduce pain is the Benson relaxation technique. This study aims to reduce pain in postpartum caesarean section patients using the Benson relaxation technique. Descriptive research with a case study approach accompanied by the application of evidence-based practices for postpartum caesarean section mothers. Application to postpartum patients aged 35 years with postpartum section on the second day. The Benson relaxation technique is carried out once a day for 2 days with a duration of 10-15 minutes. The results of the study showed that there was a significant reduction in the pain scale from a pain scale of 6 to 2. By applying the Benson relaxation technique, patients can focus more on applying the Benson relaxation technique to reduce the pain they feel and with this technique nurses can apply it to pregnant women and mothers with normal delivery.